TUBERCULOSIS IN CHILDREN AND ADOLESCENTS IN RUSSIA (PROBLEMS AND SOLUTIONS IN XXI CENTURY) - V.A. Aksenova; T.A. Sevost'yanova; N.I. Klevno; V.N. Lapshina ("Paediatrician" Publishers LLC, 2011)
The article summarizes the results of diversified epidemiological and clinical study performed in Russian Federation. The peculiarities of tuberculosis infection in modern epidemiological situation, clinical symptoms of a disease and risk factors of its development are described. New risk groups of tuberculosis infection are children who need common observation within management of inflammatory rheumatic diseases and other chronic pathology treated with immunosuppressive agents. Authors show the necessity of differentiative approach to the prophylaxis and early diagnostics of tuberculosis within phthisiologic and common pediatric healthcare services.Key words: children, tuberculosis, prevalence, risk factors.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2011; 10 (3): 7-11)